2022
DOI: 10.3390/healthcare10020282
|View full text |Cite
|
Sign up to set email alerts
|

Health Management in Italian Prisons during COVID-19 Outbreak: A Focus on the Second and Third Wave

Abstract: The SARS-CoV-2 spread is a threatening and challenging issue for correctional systems worldwide because of many factors, particularly overcrowding and of the intrinsic characteristics of the population. The prevention measures adopted by the Italian Government were aimed to protect and preserve both inmates’ and prison workers’ health. The present study aimed to evaluate the efficacy of the adopted strategies. Methods: Data regarding Italian prisons’ occupation and prisoners’ population from January 2019 to Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…In March 2021, about two months after the COVID-19 vaccines became available in Italy, by decree of the Italian Ministry of Health, prisoners as well as prison workers were included among the priority targets of the vaccination campaign due to the complexity of this population and their high risk of infection, severe disease, and death [ 19 ]. Unlike many other countries, this led to an immediate implementation of vaccinations within those categories in the Italian population [ 20 ]. At the time of the outbreak, the reported COVID-19 vaccination coverage in the investigated prisons showed 84.2% of inmates receiving at least one dose of mRNA vaccine, and 76.3% fully vaccinated, comparable to the coverage observed among Italian adults overall (83.1% and 76.3%, respectively), and the general Italian prison population at that time [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In March 2021, about two months after the COVID-19 vaccines became available in Italy, by decree of the Italian Ministry of Health, prisoners as well as prison workers were included among the priority targets of the vaccination campaign due to the complexity of this population and their high risk of infection, severe disease, and death [ 19 ]. Unlike many other countries, this led to an immediate implementation of vaccinations within those categories in the Italian population [ 20 ]. At the time of the outbreak, the reported COVID-19 vaccination coverage in the investigated prisons showed 84.2% of inmates receiving at least one dose of mRNA vaccine, and 76.3% fully vaccinated, comparable to the coverage observed among Italian adults overall (83.1% and 76.3%, respectively), and the general Italian prison population at that time [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Measures taken in such situations are legally enforceable at each national level. For example, related to the COVID-19 pandemic context, the study by Vella et al in Italy found a lower number of COVID- positive cases among detainees than among the general population, which reflected the effectiveness of the measures taken, including vaccination [ 45 ]. In the same sense, Pagano et al found that measures such as screening and safe isolation of COVID-positive or COVID-suspect detainees prevented the spread of the virus [ 46 ].…”
Section: Particular Scenarios Physician–inmate Patientmentioning
confidence: 99%
“…Italy was among the first countries in Europe to be affected by the COVID-19 pandemic [ 4 , 5 , 6 , 7 ]. This required the definition and implementation, in the shortest possible time, of management and prevention protocols, both for the Italian and prison populations.…”
Section: Introductionmentioning
confidence: 99%